Can you hear me? Impacts of underwater noise on communication space of adult, sub-adult and calf contact calls of endangered St. Lawrence belugas (Delphinapterus leucas) - Vergara, Valeria; Wood, Jason; Lesage, Véronique; Ames, Audra; Mikus, Marie-Ana; Michaud, Robert (Polar research, 2021)
Noise and anthropogenic disturbances from vessel traffic are an important threat to the recovery of the endangered St. Lawrence Estuary (SLE) beluga population. The consequences of acoustic masking could be particularly adverse in the case of critical vocalizations that maintain contact between mothers and their dependent but mobile calves. This study models the communication range of adults, sub-adults and newborn beluga contact calls in the presence and absence of vessels in an important summering area for this population. Ambient noise measurements, a composite beluga audiogram and apparent source levels of adult/sub-adult and newborn calls, informed the model. Apparent source levels were estimated from received levels of contact calls produced by four individuals carrying digital acoustic tags in the SLE, Canada, and from received levels of calls recorded from two adults and a newborn calf at an aquarium, at known distances from a calibrated hydrophone. The median communication ranges were over 18 times larger for SLE adult and sub-adult calls than for newborn calls, with a 57 and 53% reduction in range in the presence of vessel noise, respectively. For newborn calls, this results in a median range of 170 m in vessel noise. These first estimates of the communication range of beluga vocalizations with a known function suggest that masking of the quiet calls of newborns by anthropogenic noise could impair mother–calf contact.